European Union Prize for Contemporary Architecture : Mies van der Rohe Award : 2007. - Gray, Diane (Barcelona : Actar, 2007)
Mansilla+Tuñón Arquitectos / MUSAC - Contemporary Art Museum of Castilla y León ; bevk perović arhitekti / Faculty of Mathematics, Ljubljana, Slovenia ; Aires Mateus e Associados / Sines Arts Centre, Sines, Portugal ; UNStudio / Mercedes-Benz Museum, Stuttgart, Germany ; David Chipperfield Architects, b720 Arquitectos / America's Cup Building, Valencia, Spain ; Zaha Hadid Architects / Phæno Science Center, Wolfsburg, Germany ; Lacaton & Vassal Architectes / School of Management, Bordeaux, France ; Rudy Ricciotti architecte / National Choreographic Centre, Aix-en-Provence, France ; Ábalos&Herreros Arquitectos, Casariego Guerra Arquitectos / Woermann Tower, Las Palmas de Gran Canaria, Spain ; Marinaprojekt / Sea Organ, Zadar, Croatia ; Architects Bates Maher / Poustinia, Clonmel, Co. Tipperary, Ireland ; Brendeland & Kristoffersen Arkitekter / Housing Svartlamoen, Trondheim, Norway ; Caruso St John Architects / Brick House, London, United Kingdom ; Antonio Citterio and Partners / GlaxoSmithKline Day Nursery, Verona, Italy ; Clotet, Paricio i Associats / Illa de la Llum Housing at Diagonal Mar, Barcelona, Spain ; Feichtinger Architectes / Simone de Beauvoir Footbridge, Paris, France ; Foster + Partners / Free University of Berlin, Berlin, Germany ; Massimiliano Fuksas Architetto / New Trade Fair Milan, Milan, Italy ; XDGA, Stéphane Beel Architecten / University of Gent, Economics Buiding, Ghent, Belgium ; the next ENTERprise / Lakeside Bath, Caldaro-Kaltern, Italy ; Hertl.Architekten / Ecker Abu Zahra House, Luftenberg, Austria ; PLOT = BIG (Bjarke Ingels Group) + JDS (Julien De Smedt Architects) / VM Houses, Copenhagen, Denmark ; Jensen & Skodvin Arkitektkontor / New Monastery for Cistercian Order, Tautra, Norway ; Antonio Jiménez Torrecillas / Intervention on the Nasrid Wall, Upper Albaicín, Granada, Spain ; JHK Architecten / deBrug, Rotterdam, Netherlands ; Enota / Hotel Sotelia, Podčetrtek, Slovenia
scape architecture, Klein & Baumann Architectes / West School Complex, Obernai, France ; Josep Llinàs / Jaume Fuster Library, Barcelona, Spain ; Miralles Tagliabue - EMBT / Santa Caterina Market Renovation, Barcelona, Spain ; Neutelings Riedijk Architecten / Shipping and Transport College, Rotterdam, Netherlands ; Ateliers Jean Nouvel, b720 Arquitectos / Agbar Tower, Barcelona, Spain ; White / Kastrup Sea Bath, Copenhagen, Denmark ; Randić-Turato Architects / Fran Krsto Frankopan Elementary School, Krk, Croatia ; Richard Rogers Partnership, Estudio Lamela / Terminal 4 Madrid Barajas Airport, Madrid, Spain ; sauerbruch hutton / Federal Environmental Agency, Dessau, Germany ; Studio Maarten Van Severen / Garden Pavilion for the Boxy Cartering Company, Deurle, Belgium ; Büro für Architektur und Forschung / Fluc 2, Music and Art Club: Transformation of a Pedestrian Underpass, Vienna, Austria ; Ecosistema urbano arquitectos / Ecoboulevard of Vallecas, Madrid, Spain ; Mimarlar Tasarim / SM House, Çanakkale, Turkey ; Wandel Hoefer Lorch + Hirsch archtekten / Documentation Centre, Hinzert, Germany
boek